Physicochemical stability of ternary admixtures of butorphanol, ketamine, and droperidol in polyolefin bags for patient-controlled analgesia use - Fang BX; Wang LH; Gu JF; Chen FC; Shi XY (Dove Medical Press, 2016)
Baoxia Fang,1 Linhai Wang,2 Junfeng Gu,3 Fuchao Chen,1 Xiao-ya Shi1 1Department of Pharmacy, Dongfeng Hospital, 2Department of Pharmacy, 3Department of Anesthesiology, Renmin Hospital, Hubei University of Medicine, Hubei, People’s Republic of China Background: Delivery of drug admixtures by intravenous patient-controlled analgesia is a common practice for the management of postoperative pain; however, analytical confirmation of the compatibility and stability of butorphanol tartrate, ketamine hydrochloride, and droperidol combined in ternary admixtures is not available.Methods: Butorphanol tartrate, ketamine hydrochloride, and droperidol have been examined for compatibility and stability when combined with 0.9% sodium chloride injection stored at 4°C and 25°C with light protection for a total of 14 days. Concentrations were 0.067 mg/mL, 1.33 mg/mL, and 0.033 mg/mL for butorphanol tartrate, ketamine hydrochloride, and droperidol, respectively. Drug concentrations were determined using high-performance liquid chromatographic analysis.Results: All three drugs were very stable (>97%) at 4°C and 25°C for 14 days. The ternary admixtures were initially clear and colorless throughout the observation period, and the pH value did not change significantly.Conclusion: The results confirm that the ternary admixture of butorphanol tartrate 0.067 mg/mL, ketamine hydrochloride 1.33 mg/mL, and droperidol 0.033 mg/mL in 0.9% sodium chloride injection were stable for 14 days when stored in polyolefin bags at 4°C and 25°C and protected from light. Keywords: analgesia, patient-controlled analgesia, drug stability, butorphanol, ketamine, droperidol, HPLC